Wandering With/In the University of Alberta: Teaching Subjects & Place-based Truth & Reconciliation Education - Madden, Brooke; Michaud, Craig Kenneth; Edgar, Tarah; Jones, Jennifer (Alberta Journal of Educational Research, 2020)
This manuscript unfolds in the context of a Faculty of Education course that was designed in response to the Truth and Reconciliation Commission of Canada’s call to post-secondary institutions to identify and meet teacher-training needs relating to the history and legacy of Canada’s Indian residential school system. The course instructor (Madden) begins by tracing how she is theorizing truth and reconciliation education through engagement with literature produced by the Truth and Reconciliation Commission of Canada, and those who respond to their efforts. The pedagogical activity Wandering With/In the University of Alberta animates how she attempted to mobilize these emerging understandings through course design. We then introduce the collective processes we carried out as co-authors (i.e., course instructor and three graduate students who completed the course): creating, analyzing, and representing data, as well as generating the knowledge claims offered throughout. Next, data fragments that weave photographs of and narrative writing about campus sites anchor exploration of three central themes: wandering in relation to (a) evolving understandings of self, (b) a situated and significant historical moment (i.e., Canada 150), and (c) the (imagined) classroom as a site of reconciliation. We conclude with a discussion that explores the relationship between Faculty of Education coursework, identity, and place-based pedagogies for truth and reconciliation education. Keywords: truth and reconciliation education, higher education, decolonizing, place-based education, teacher identity Cette étude s’est déroulée dans le contexte d’un cours offert par la Faculty of Education et développé en réponse à l’appel de la Commission de vérité et réconciliation du Canada aux établissements postsecondaires pour qu’ils identifient les besoins en formation des enseignants quant à l’histoire et les séquelles du système des pensionnats indiens au Canada et qu’ils répondent à ces besoins. La chargée de cours (Madden) débute en expliquant ses démarches pour théoriser l’éducation de vérité et réconciliation en se penchant sur la littérature produite par la Commission de vérité et réconciliation du Canada et sur la réaction des gens aux efforts de la commission. L’activité pédagogique Wandering With/In the University of Alberta est une animation de ses efforts pour mobiliser ces nouvelles connaissances par la conception de son cours. Ensuite, nous présentons les processus collectifs que nous avons entrepris comme co-auteurs (c’est-à-dire, la chargée de cours et les trois étudiants aux études supérieures ayant complété le cours): la création, l’analyse et la représentation des données, ainsi que l’élaboration des déclarations présentées dans l’ensemble du cours. Par la suite, des fragments de données tissent des photos et des récits narratifs portant sur des sites sur le campus et offrent des balises pour l’exploration de trois thèmes centraux: errer par rapport à: (a) une compréhension en évolution de soi-même, (b) un moment historique significatif (par ex., Canada 150) et (c) la salle de classe (imaginée) comme site de réconciliation. Une discussion portant sur le rapport entre les cours de la Faculty of Education, l’identité et les pédagogies reposant axées les lieux au service de l’éducation de vérité et réconciliation vient terminer l’article. Mots clés: éducation de vérité et réconciliation, études supérieures, décolonisation, identité des enseignants